A Cohort Study of One-Year Functional and Radiographic Outcomes following Intra-Articular Distal Radius Fractures. (June 2014) - Lalone, Emily A.; Rajgopal, Vaishnav; Roth, James; Grewal, Ruby; MacDermid, Joy C.
Background: The purpose of this study was to describe the outcomes of a series of patients followed prospectively after intra-articular distal radius fractures. Methods: One hundred forty-eight patients with intra-articular fractures (mean age, 47 years; age range, 44–54 years; gender distribution, 60 males and 88 females) were treated with cast only, arthroscopy/closed reduction plus pins, arthroscopy/closed reduction with external fixation, open reduction and internal fixation (ORIF) alone, and ORIF with external fixation according to surgeon preference and fracture characteristics. The 1-year outcomes across the groups were measured radiographically ( n =148) and functionally ( n =113; 1-year Wrist Outcome Measure score, Grip Strength, SF-36, and PRWE scores). Results: Radiographically, the groups had statistically significant differences in radial inclination, volar tilt, intra-articular step-off, and radial shortening in the pre-treatment X-rays. However, following treatment, treatment groups demonstrated no difference statistically in their follow-up radiographic measures. One-year PRWE scores were found to be statistically different across groups. Across groups, the ORIF-alone treatment group had the highest PRWE score reflecting greatest amount of pain and disability. One-year wrist outcome measure scores and grip strength scores were also found to be significantly different across treatment groups. The general health status as measured by the SF-36 was not found to be different across treatment groups. Conclusions: These findings are consistent with treatment by indication; suboptimal ORIF outcomes may reflect older practice patterns with dorsal plating. A randomized control trial that compares treatments controlling for fracture severity and studies that develop formal clinical prediction rules for treatment assignment are needed.